Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Spare Part Alat Berat PT. Indotruck Utama Pada Konsumen Di Provinsi Jawa Timur - Yogo Subekti; Arga Christian Sitohang (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research applies a quantitative approach to determine the influence of customer income, price of goods, and quality on demand for PT heavy equipment spare parts. Indotruck Utama to consumers in East Java. The research method used is multiple linear regression analysis, with the help of SPSS analysis tools to test the hypothesis. In the results of this research, it was found that the results of the F Test simultaneously showed that the variables income (X1), price (X2), and quality (X3) together could influence the demand variable. Based on the results of the t test, it shows that the income variable (X1) partially has a significant effect on the demand variable, while the price variable (X2) and quality variable (X3) partially have no effect and are not significant on the demand variable (Y).